Revision of The Genus Eria (Orchidaceae) in Peninsular Malaysia - Tang, Cher Hing (2007)
The genus Eria which was reported consists of 49 species in 11 sections in Peninsular Malaysia was revised. Findings from previous studies, ranging from diversity, vegetative architecture to molecular and morphological evidences have been used to solve the taxonomic problems in this genus. However, the sections and species delimitation for genus Eria are still obscure especially Section Aeridostachya, Urostachya, Mycaranthes and Hymeneria, despite of the many approaches attempted to delimit them. This study was carried out based on traditional taxonomic analysis on. fresh and dried herbarium specimens and spirited collections targeted to investigate and gather as much as possible gross morphological characteristics of vegetative and floral organs that could be utilized to delimit sections and species of Eria in Peninsular Malaysia. The vegetative characters investigation includes the growth habit, stem or pseudoulbs and leaves whilst; the floral characters include the inflorescences, the details of flower parts like sepals, petals and lip. There are two types of growth habit observed, the creeping and aggregate either with stems or pseudobulbs. A total of six leaf shape found, which are attached to the stem or peseudobulb by sheathing or auriculate-clasping. The investigation on the inflorescence shows that Eria has four inflorescence types, the solitary, bifloral, raceme and compound corymb. The inflorescence insertions were observed with three kinds, the terminal, subterminal and axillary. The flower characteristics include the shape of the flower, lip and pollinia has been studied under the light microscope for each species from every section. The ventral lip surface and pollen were studied under the Scanning Electron Microscope (SEM). There are 11 types of flower shapes representing each section ranging from Stellate A, Stellate B, Stellate C, Stellate D, Stellate E, Palmate, Campanulate A, Campanulate B, Campanulate C, Conical and Peltate. There are 11 types of lip shape representing each section, ranging from hastate, praemorse, lingulate, obovate, 'pendulum' shape, rotund, 'tie' shape, obstrullate, 'mushroom' shape, lobatus and rhomboid. Five types of pollinia shapes have been discovered are clavate, conical, square, narrow pyriform and compress conical. The flower shape and lip shape are good characters for section delimitation, while the pollinia shape is a good character for species delimitation. The SEM on pollen for Eria shows similar results for all species, the monolete shape with irregular ridges of sexine and laevigate sculpture, thus SEM on Eria pollen is a bad character for species and section delimitation. The SEM on ventral lip surface for Eria shows homogeneous or heterogeneous glabrous or with six types of papillae hairs. The shape of the papillae hairs are conical, narrow spatulate, broad spatulate, spherical, clavate and villiform. The SEM for ventral lip surface is bad taxonomic character for species and section delimitation. E. ochracea is added as a new record for Peninsular Malaysia, The taxonomic keys were successfully developed using the vegetative and floral characteristics gathered in this study.